Convective flow of a fractional second grade fluid containing different nanoparticles with Prabhakar fractional derivative subject to non‐uniform velocity at the boundary. (9th May 2021) - Basit, Abdul; Asjad, Muhammad Imran; Akgül, Ali
Abstract : This article disputes the study of convective flow for improved nanofluid along with an erect heated plate via Prabhakar‐like energy transport. The governing equations for this mathematical model are obtained by Prabhakar fractional derivative. To attain the generalized results for dimensionless velocity profile and temperature profile, a scheme of Laplace transform is applied. By applying the conditions of nanofluid flow, we develop the constantly accelerated, variables accelerated, and non‐uniform accelerated solution of the model. Prabhakar fractional derivative for improved nanofluid based on generalized Fourier's thermal flux is determined for heat transfer. Different structures of graphs are performed for ordinary fractional parameters. As a result, it is found that temperature of Ag  −  H 2 O is higher than Cu  −  H 2 O and TiO 2  −  H 2 O nanoparticles and the reverse trend can be found for velocity. Furthermore, temperature and velocity can be enhanced by increasing the values of fractional parameters.